Exporting Raymond - Rosenthal, Phil, 1960- (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
Follows television producer Phil Rosenthal as he travels to Russia to help a crew produce the Russian equivalent of the American program "Everybody loves Raymond."
Originally released as a motion picture in 2010.
Features: Compare "Everybody loves Raymond" to "Everybody loves Kostya," commentary with writer/director Phil Rosenthal, deleted scenes, theatrical trailer.
DVD, Dolby digital 5.1 surround.
In English with optional English, French, or Spanish subtitles.
Closed-captioned.
Keywords: Everybody loves Raymond (Television program); Television producers and directors -- United States; Television producers and directors -- Russia (Federation); Documentary films; Video recordings for the hearing impaired; Nonfiction films; Feature films